Strengthening Protective Skills Through SmartShield Web-based Interactive Modules - Mohamad Najib Mat Pa; Anisa Ahmad; Mohd Nor Norhayati; Zaharah Sulaiman; Nik Hazlina Nik Hussain; Azizah Othman; Azliana Aziz (Education in Medicine Journal, 2026)
Child sexual abuse is a serious public health issue, yet protective skills against sexual abuse are poorly addressed in the Malaysian primary school curriculum. This study evaluated the effectiveness of SmartShield modules in enhancing these skills among Malaysian primary school students. A quasi-experimental controlled trial used stratified multistage cluster sampling. Six government primary schools were randomly selected across five regions. Within each school, one lower- and one upper-primary class was selected. The sample size, calculated by comparing two means, included 912 children for SmartShield 1 and 912 children for SmartShield 2. SmartShield 1 consisted of two modules, while SmartShield 2 consisted of a single module. Skills were assessed at baseline, after Week 2, and after Week 4 based on validated questionnaires. Data were analysed using repeated measures analysis of variance (ANOVA), adjusted for sex and region. For lower primary, the response rates for the intervention and control groups were 96.5% (440/456) and 96.7% (441/456), respectively. For upper primary, the respective rates were 96.7% (441/456) and 95.6% (436/456). The intervention group showed significant improvements in skills scores across all modules (p < 0.001), indicating the effectiveness of the SmartShield programme. In lower primary, adjusted mean scores increased from 87.6% to 98.5% in the intervention group versus 90.3% to 94.8% in the control group. In upper primary, scores improved from 91.3% to 98.9% (intervention) versus 85.7% to 97.0% (control). The SmartShield programme was effective in enhancing child sexual abuse prevention skills among Malaysian primary school children.